2021
DOI: 10.47080/joubahs.v1i02.1480
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Paparan Alergen Tungau Debu Di Lingkungan Sekolah Terkait Dengan Sensitisasi Alergi Di Sekolah Dasar Di Serang Tahun 2021

Abstract: Tungau debu merupakan salah satu aeroalergen yang paling umum yang memiliki hubungan kuat dengan manifestasi dan sensitisasi alergi. Paparan alergen di sekolah dapat menyebabkan sensitisasi dan memicu penyakit atopik dan manifestasi alergi, sehingga menurunkan prestasi belajar siswa di sekolah. Perlu dilakukan penelitian lebih lanjut untuk menganalisis kualitas udara dalam ruangan sekolah terkait tungau debu dan pengaruhnya terhadap sensitisasi alergi pada siswa. Penelitian ini bertujuan untuk mengetahui hubun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This was similar with a study of adult AD patients in Indonesia that found the sensitization to HDM was 55.2% (Suwarsa, et al, 2017). In normal population, the sensitization to HDM ranged from 17.8% to 26.1% (Sundaru, 2016;Ambarwati and Ferial, 2021) The assessment of clinical relevance might lead to more useful findings for clinicians and patients, improving the use of information in clinical practice (Armijo-Olivo et al, 2011). The clinical relevance of IgE-mediated sensitizations must be carefully assessed because positive SPTs may not always indicate allergies.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar with a study of adult AD patients in Indonesia that found the sensitization to HDM was 55.2% (Suwarsa, et al, 2017). In normal population, the sensitization to HDM ranged from 17.8% to 26.1% (Sundaru, 2016;Ambarwati and Ferial, 2021) The assessment of clinical relevance might lead to more useful findings for clinicians and patients, improving the use of information in clinical practice (Armijo-Olivo et al, 2011). The clinical relevance of IgE-mediated sensitizations must be carefully assessed because positive SPTs may not always indicate allergies.…”
Section: Discussionmentioning
confidence: 99%